Predictors of ethical decision-making among young accountants: Evidence from Vietnam - Thi, Thanh Hai Nguyen; Tran, The Nu; Minh, Phuong Nguyen; Nguyen, Thu Hien; Nguyen, Hoang An (Edelweiss Applied Science and Technology, 2026)
This study examines the predictors of ethical decision-making among young accountants in Vietnam by focusing on the sequential relationship between moral awareness, moral judgment, and ethical intention. Drawing on Rest [1]’s moral decision-making framework and Hofstede’s concept of power distance, the study investigates how education, gender, power distance, and risk-taking propensity are associated with ethical cognition in an emerging-market context. Using survey data from 194 respondents, including accounting and auditing students as well as early-career auditors, the study applies structural equation modeling (SEM) to test the proposed relationships. The results provide support for an awareness-judgment-intention pathway in ethical decision-making. Gender, power distance, and risk-taking propensity were found to significantly influence moral awareness, while moral awareness strongly affected moral judgment, which in turn significantly shaped ethical intention. The findings also suggest that education-related effects are more nuanced, with professional exposure and academic seniority showing more evident associations with ethical cognition than education as a single overall factor. Overall, the study indicates that both individual characteristics and cultural orientation contribute to ethical decision-making among young accountants in Vietnam. By providing evidence from a non-Western and underexplored context, the study contributes to the accounting ethics literature and offers implications for ethics education and professional development in Vietnam’s accounting sector.